Analysis of the Gut Microbiota and Inflammatory Factors in mGluR5-Knockout Mice - Cai, Guohong; Zhu, Yuanyuan; Chen, Jing; Zhao, Suo; Wang, Liying; Wang, Mengmeng; Huang, Jing; Wu, Shengxi (Frontiers in Psychiatry, 2020)
Introduction: Accumulating evidence indicates that the glutamatergic system plays a critical role in the pathophysiology of depression. Notably, the antidepressant effect of metabotropic glutamate receptor 5 (mGluR5) modulation is inconsistent across studies. Here, we attempted to identify the involvement of the gut microbiota and inflammation in mGluR5-/- mice. Methods: mGluR5−/− mice and their wild-type littermates were used in our study. We used the open field (OF) and elevated plus maze (EPM) tests to assess anxiety-like behaviors. We used the two-day forced swim test (FST) and tail suspension test (TST) to test depression-like behaviors. 16S rDNA was used to analyze the gut microbiota. Enzyme-linked immunosorbent assays (ELISAs) were used to measure the levels of inflammatory factors. Western blotting was used to detect the levels of various proteins in the brain. Results: mGluR5−/− mice had no significant depression-like or antidepressant behavior in the absence of stress exposure. However, mGluR5−/− mice exhibited depression-like behaviors following stress exposure. No significant changes in other glutamate receptors or representative synaptic proteins were detected in the prefrontal cortex (PFC) or hippocampus of mGluR5−/−mice. Very similar bacterial groups were observed in mGluR5−/−mice and wild-type controls. In addition, there was no significant difference in the α diversity of the microbiota between mGluR5−/− mice and wild-type controls. The levels of all 6 measured cytokines (IL-1β, IL-2, IL-4, IL-6, IL-10 and TNF-α) did not change significantly in the PFCs or colons of mGluR5−/− mice. Conclusion: In conclusion, we deduced that mGluR5−/− mice are susceptible to depression-like behavior. The systemic knockout of mGlur5 did not affect the gut microbiota or inflammatory factors in mice.